Daddy's gone a hunting - Clark, Mary Higgins; Maxwell, Jan, 1956- (New York : Simon & Schuster Audio, 2013)
In this new novel, a dark secret from a family's past threatens the lives of two sisters, Kate and Hannah Connelly.
Cataloged from vendor record.
Compact discs.
Duration: ca. 9:00:00.
Read by Jan Maxwell.
Keywords: Family-owned business enterprises -- Fiction; Arson investigation -- Fiction; Murder -- Investigation -- Fiction; Audiobooks; Mystery fiction; Suspense fiction